Microwave-Induced, Iodine-Alumina Catalyzed Transformations of 1-(2′-hydroxyaryl)-3-(2-chloroquinolin-3-yl)-prop-2-en-1-one - P. Venkatesan; K. Moorthi (E-Journal of Chemistry)
The chalcone derivatives, 1-(2′-hydroxyaryl)-3-(2-chloroquinolin-3-yl)-prop-2-en-1-one was transformed to corresponding flavone derivatives by iodine impregnated neutral alumina under microwave irradiation. The synthesized flavone derivatives were structurally confirmed by elemental analysis, UV, IR and 1H-NMR spectral data, and the notable yield obtained was compared with previously reported method.